Comparison of effectiveness and safety of lasmiditan and CGRP-antagonists for the acute treatment of migraine in adults: systematic review and network meta-analysis of randomised trials - Xinxin Deng; Liying Zhou; Cui Liang; Xue Shang; Xu Hui; Wendi Liu; Shanshan Liang; Yongsheng Wang; Meng Xu; Kangle Guo; Kehu Yang; Xiuxia Li (The Journal of Headache and Pain, 2024)
Abstract Objective To compare the outcomes associated with the use of lasmiditan, rimegepant, ubrogepant, and zavegepant for the acute management of migraine headaches. Methods We searched four electronic databases from database inception to August 31, 2023, to identify randomized controlled trials (RCTs) that report efficacy and safety for the acute treatment of migraine. The risk of bias in the included RCTs was evaluated according to the Cochrane tool, and the certainty of evidence using the CINeMA approach. We conducted frequentist network meta-analyses (NMA) to summarise the evidence. Data were analyzed using R-4.3.1. Results A total of 18 eligible studies including 10 different types of interventions with 22,429 migraine patients were included. NMA results showed that compared to ubrogepant (25 mg and 50 mg) and zavegepant, lasmiditan (100 mg and 200 mg) exhibits an elevated probability of achieving pain relief within a 2-hour interval. Similarly, relative to zavegepant, rimegepant (75 mg) and ubrogepant (50 mg and 100 mg) demonstrate an enhanced likelihood of sustaining pain relief over a 24-hour period. Furthermore, in contrast to ubrogepant (25 mg) and lasmiditan (50 mg), rimegepant (75 mg) presents a heightened probability of achieving freedom from photophobia within 2 h. Regarding safety, lasmiditan carries the highest risk of adverse events, which are associated with an increased incidence of adverse effects, including dizziness, somnolence, asthenia, paresthesia, and fatigue. Conclusions In this NMA, a spectrum of evidence ranging from very low to high levels underscores the favorable efficacy and tolerability of rimegepant 75 mg and ubrogepant 100 mg, positioning them as potential candidates for the acute management of migraine. Concurrently, lasmiditan (100 mg and 200 mg) exhibits notable efficacy, albeit accompanied by an increased susceptibility to adverse events. These findings should still be approached with caution, primarily due to the intrinsic limitations associated with indirect comparisons.